(untitled) (Cadernos de Filosofia Alemã: Crítica e Modernidade, 2012)
Here I discuss the necessity of establishing a history of philosophy which resorts only to the study of documents of philosophical interest, if this history is supposed to be useful for our understanding certain philosophical notions according to their historical development. To do so, I first show that in the very moment in which a historical narrative presupposes a logical level besides its documental level, it loses its usefulness. After that, I point out the way in which we can narrate an exclusively documental history of philosophy.